Management of Amavata by Langhana Therapy-A Single Case Study. - Aleena, M N; Ravoof P K (International Research Journal of Ayurveda & Yoga, 2023)
Amavata is a common crippling and disabling disorder which affects the functional mobility of the patient in jeopardy. Amavata has symptoms similar to Rheumatoid Arthritis. RA has a prevalence of approximately 0.8% of the population, where women are affected 3 times more than the men. Recent reports suggest that RA affect about 1% of world population. Even in allopathic medicine, there is no current complete cure to RA, but managed with mere pain killers and immune suppressing therapies, long term use of which leads to many side effects. In Ayurvedic classic, the general principle for the management of Amavata mentions procedures like Langhanam (Reduction) Swedanam(Sudation) (mainly Ruksha Swedana),Deepana Aushadas (Kindling medicine)like Katu, Thikta aushad (medicine with tiktha katu rasa), Deeepana (kindling),Virechana (purgation), Snehapana (oelation),Vast(panchakarma procedure).This article is a review of Ayurvedic management of Amavata where only Langhana(reduction) line of treatment for Amavata is used, It is considered as the first line of treatment .This article is written to emphasise the role of Langhana Upakrama in Aamavata management without using any one of the Bhrimhana Upakramas(Nourishment therapies).Here a case report of Amavata treated for a period of 16 days and thereby achieving remarkable reduction in pain and swelling with Langhana (Reduction)line of management is explained. Also, a follow up for a period of 1 month is taken where the patient had no recurrence of similar joint pains and swellings.